2011
DOI: 10.1002/pc.21191
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of POM thermooxidation resistance through POSS nanoparticles

Abstract: Thermooxidative degradation at and beyond processing temperatures has been carried out on polyoxymethylene (POM) enhanced with four different types of POSS, being Glycidyl, GlycidylIsobutyl, Aminopropylisobutyl, and Poly(ethylene glycol). The quantification of such degradation was carried out through FTIR spectrography, color spectrophotometry, and thermogravimetric analysis methods. The results showed that the presence of POSS in the blend improves dramatically the thermal stability of the POM matrix. The bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…Hence, Sánchez-Soto and co-workers [11,19] investigated the influence of the four different types of polyhedral oligomeric silsesquioxanes (POSS) on the thermooxidative resistance of POM-based nanocomposites and they found that addition of amino functionalized POSS leads to an increase of the thermal decomposition temperature up to 50°C. In another work, effects of carbon nanotubes on processing stability of POM in meltmixing process were studied [20]; the addition of functionalized carbon nanotubes leads to a drastic degradation of POM as the presence of carboxylic acid groups on CNT surfaces catalyzes and accelerates the polymer degradation through acidolysis and hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Sánchez-Soto and co-workers [11,19] investigated the influence of the four different types of polyhedral oligomeric silsesquioxanes (POSS) on the thermooxidative resistance of POM-based nanocomposites and they found that addition of amino functionalized POSS leads to an increase of the thermal decomposition temperature up to 50°C. In another work, effects of carbon nanotubes on processing stability of POM in meltmixing process were studied [20]; the addition of functionalized carbon nanotubes leads to a drastic degradation of POM as the presence of carboxylic acid groups on CNT surfaces catalyzes and accelerates the polymer degradation through acidolysis and hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…It has a wide range of applications mainly in automotive, electrical and mechanical industry [1,2]. However, POM is inherently unstable because its repeating oxymethylene units are usually terminated with thermally unstable hemi-formal terminals [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These advantages were considered when modifying POM by the incorporation of fully condensed POSS cages glycidylethyl-POSS, aminopropylisobutyl-POSS, and poly(ethylene glycol)-POSS, octaisobutyl-POSS, and glycidylisobutyl-POSS (Figure 6.4) through direct melt blending. The best results were found for POM composites with aminopropylisobutyl-POSS-the onset of degradation temperature increased by more than 50 °C (Ramirez et al, 2011). The best results were found for POM composites with aminopropylisobutyl-POSS-the onset of degradation temperature increased by more than 50 °C (Ramirez et al, 2011).…”
Section: Pom/poss Nanocompositesmentioning
confidence: 93%